Educational Self-regulation Prediction Based on the Components of the Attribution Styles among Secondary School Students in Sari City in Northern Iran - Khairulnesa Shirdel; Mohammad-Kazem Fakhri; Bahram Mirzaian (Shahid Beheshti University of Medical Sciences, 2020)
Background and Objectives: One of the motivational-cognitive factors influencing various aspects of human life such as learning and academic achievement is attribution style. The purpose of this study was to predict educational self-regulation based on the components of attribution style among students. Materials and Methods: The research was of descriptive-correlational design and the statistical population included all secondary school students in the city of Sari in northern Iran during the 2016-2017 academic year, among whom 375 students were selected using cluster and stratified sampling. Among participants 160 were boys and 215 girls. The data collection tool was the self-regulatory questionnaire and the attribution style questionnaire (ASQ). Pearson correlation coefficient and multivariate regression analysis using SPSS software version 22 were used to analyze data. Results: The mean (SD) age of boys was 16.4 (3.4) and girls 16.8 (3.7). By increasing the score of attribution styles with the mean (SD) 147.9 (15.2) and its components including locus of control with the mean (SD) 49.7 (6.7), stability 49.2 (6.0) and comprehensiveness 48.9 (7.9), student's self-regulation with the mean (SD) 45.5 (7.9) increased (P<0.01). In addition, the locus of control component predicted self-regulation (P<0.001). However, stability and comprehensiveness did not predict self-regulation. Conclusion: The study showed that by the increase in the score of documentary styles, self-regulation increased. In addition, the source of control from the variable components of attribution styles predicted student self-regulation. DOI: http://doi.org/10.22037/ch.v7i2.25256